Atividade inseticida de pós de vegetais e do gesso em relação ao caruncho do feijão, Zabrotes subfasciatus (Boheman, 1833) (Coleoptera: Chrysomelidae) - Carvalho, Luiz Henrique Torres de (2008)
Bean weevil, Zabrotes subfasciatus (Boheman, 1833) (Coleoptera: Chrysomelidae) is considered the main insect-pest of the stored beans. Currently its control is achieved through protective spray (fumigations). New techniques of alternative control are being used to minimize the use of insecticides such as the use of resistant cultivars and insecticide plants through powders, extracts and oils. This work was divided into four chapters. The first consisted of a review of literature. In the second evaluated the method of control through the use of powders plants of different parts of plants from three species of the genus Annona, seeds powders of Piper nigrum L. and plaster. In the third it has developed a method of control through the use of powders plants of different parts of plants from three species of the genus Annona; powder seeds of Piper nigrum L.; Ageratum conyzoides L. (branch and leaf); Ricinus communis L. (leaf) and Azadirachta indica A. juss associated with plaster. And the fourth was tested after four species of plants: Piper nigrum L., Chenopodium ambrosioides, Coriandrum sativum L. and Cymbopogon citratus (DC) Stapf and plaster. All experiments were conducted aiming to observe possible adverse effects of these materials on the Z. subfasciatus. In general, two couples of newly emerged adults, Z. subfasciatus were placed in plastic pots of 250 mL. Where in the second chapter was used 10 g of beans, mixed with 1 g of the powder of each anonácea (leaves and branches, individually), the black pepper powder and plaster. The third chapter 10 g of beans, mixed with 0.5 g of powder of each treatment and 0.5 g of plaster, thereby completing 1 g of different powders of plants associated with plaster. In the forth chapter 5 g of the bean group Rio, at concentrations of 0.5, 0.25; 0125 g of powder per container. Were evaluated in the second chapter: cumulative mortality of first-eighth day, oviposition in the thirteenth day and quantity of emergence holes in the eighth fortieth day after the installation of bioassays. In the third chapter: cumulative mortality of first-ninth day (alternate days), oviposition on the fifteenth day, number of emergence holes in fortieth seventh day, after the installation of the bioassays, and the fourth chapter: mortality, oviposition, emergency in 2º generation of adults, number of beans with eggs deposited on the surface by adults emerged and repellency of Z. subfasciatus. In the second chapter more effective treatments were the powder of black pepper, causing rapid death in adults and consequently lower numbers of eggs and emergence holes in the grains. In the third chapter was the most effective treatment the powder of the black pepper, causing rapid death in adults and also interfered in oviposition and the number of holes for emergencies of insects. And in the last chapter found that the powder of P. nigrum L. and C. ambrosioides showed highly toxic effect on adults of Z. subfasciatus causing 100% of death until the 5º day, not providing fertile eggs in grain treated with these materials, the emergence of adults impossible to Z. subfasciatus in the three concentrations were tested and repellents for adults, the concentration of 0.25 g / 5 g beans. The peak of oviposition occurred at 4 and 5 days after the emergence of adults of Z. subfasciatus. For the other powder, did not interfere in the variables analyzed, because the treatment did not differ statistically witness except in the variable repellency of Z. subfasciatus, because based on the Index of Preference of the powder C.citratuswa srepellent.